2004
DOI: 10.1021/jp030837r
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene. Experimental Evidence for New Assignments of Electronic Transitions in the π → π* Energy Region. Absorption and Magnetic Circular Dichroism Measurements with Synchrotron Radiation

Abstract: An exploration of the vacuum ultraviolet magnetic circular dichroism and absorption spectra of propylene and a comparison to ethylene spectra provides new information on the electronic structure of ethylene. Ethylene has three electronic transitions in the energy region previously assigned as two. The presently proposed assignments for these transitions are π → 3s(1Ag → 1B3u), π → π*(1Ag → 1B1u), and π → 3p. The lowest energy transition that was previously assigned as the beginning of the π → π* is assigned as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 69 publications
3
21
1
Order By: Relevance
“…4 Recently, reexamination of the absorption and MCD spectra of ethylene was performed by Snyder et al, and they reported that the 1 1 B 1u ͑-* ͒ and the 1 1 B 3u ͓-Ryd͑3s͔͒ states have the opposite MCD signs. 54 Our results support this finding, as well Tables II and III, respectively, where the corresponding experimental values of the B terms are also given. Only the Faraday B terms are nonzero for these molecules.…”
Section: Comparison Between the Sos And Fp Methodssupporting
confidence: 87%
“…4 Recently, reexamination of the absorption and MCD spectra of ethylene was performed by Snyder et al, and they reported that the 1 1 B 1u ͑-* ͒ and the 1 1 B 3u ͓-Ryd͑3s͔͒ states have the opposite MCD signs. 54 Our results support this finding, as well Tables II and III, respectively, where the corresponding experimental values of the B terms are also given. Only the Faraday B terms are nonzero for these molecules.…”
Section: Comparison Between the Sos And Fp Methodssupporting
confidence: 87%
“…The 7.7 eV photon energy lies near the maximum of ethylene's broad first absorption band which is dominated by the π → π * transition. 38,39 We selected only the 5th harmonic for pump and probe arms by inserting an interference filter (Acton Research 160-N) in both arms of the SMI. Photo-ions from the focal region are measured with a time-of-flight ion mass spectrometer (TOF).…”
Section: Methodsmentioning
confidence: 99%
“…The 7.7 eV photon energy lies near the maximum of ethylene's broad first absorption band which is dominated by the ππ* transition. 38,39 We selected only the 5th harmonic for pump and probe arms by inserting an interference filter…”
Section: Methodsmentioning
confidence: 99%
“…An IR band at 985 cm −1 was assigned to the Si C bond stretch vibration, indicating that the Si C bond is weaker than a regular C C bond. Moreover, the UV spectrum of H 2 Si CH 2 has an absorption maximum that corresponds to the * transition at 258 nm [17], and which is redshifted by approximately 100 nm when compared to ethylene [18]. Its first ionization potential is 8.9 eV [19], which is 1.6 eV less than that of ethylene [20].…”
Section: Properties Of the Parent Silene H 2 Si Chmentioning
confidence: 99%